Dynamics of an Active Earthflow Inferred From Surface Wave Monitoring. Issue 8 (14th August 2018) - Bertello, Lara; Berti, Matteo; Castellaro, Silvia; Squarzoni, Gabriela
Abstract: Earthflows are clay‐rich, slow‐moving landslides subjected to periodic accelerations. During the stage of rapid movement, most earthflows exhibit a change in behavior from a solid to a fluid‐like state. Although this behavior has been extensively documented in the field, the mechanism leading to the rapid acceleration of earthflows is still poorly understood. Some studies suggest that earthflows essentially behave as Coulomb plastic solids, attributing the flow‐like appearance to distributed internal shearing; others believe that these landslides can be treated as viscous fluids, pointing out that the material undergoes a phase transition by increasing its moisture content. Minimal data are currently available to support these different findings. In this study, we present the results of periodic and continuous measurements of Rayleigh wave velocity carried out in an active earthflow located in the northern Apennines of Italy. Our data indicate that the material undergoes significant changes in shear stiffness and undrained strength during rapid movements. In particular, the material exhibits a substantial drop of Rayleigh wave velocity as the earthflow accelerates, followed by a slow return to predisturbance Rayleigh velocities as the landslide decelerates. Soon after a surge, the earthflow material is extremely soft and the estimated gravimetric water content is above the liquid limit. In the following months, the shear stiffness gradually increases and the water content decreases to the plastic limit following a nonlinear trend typical of a consolidation process. These data demonstrate that the earthflow transforms into a viscous fluid by softening of the material and by water entrainment. Key Points: The earthflow material at our study site undergoes significant changes in shear stiffness during rapid movements Rayleigh velocity decreases as the earthflow accelerates, then gradually increases through time as the landslide decelerates Internal deformation clearly played an important role in the dynamics of the Montevecchio earthflow